SECURITY AND DEFENSE IN NATIONAL RESILIENCE STUDIES TO REALIZE A NATIONAL SECURITY SYSTEM - Mardhani, Dewie; Runturambi, Arthur Josias Simon; Hanita, Margaretha (Jurnal Pertahanan dan Bela Negara, 2020)
Security comes from Latin, secures which means free from danger, fear, and threats which consist of traditional and non-traditional security approaches. Defense is defined as the main instrument of a country to create national security. National defense is defined as a dynamic condition of a country that covers all aspects of national life to deal with threats. National security encompasses the security of the state, society and individuals. There are still several definitions from several experts regarding the concepts of security and defense to date. This article analyses the forms of contemporary threats related to security and defense and explains their similarities and differences in the study of national resilience aimed at realizing a national security system and development of the national security system in other countries. This article uses a descriptive qualitative research design through literature study and interviews. This article explains that the forms of threats that occur in Indonesia include problems at the border area, SARA intolerance, inequality in bureaucratic reform, not optimal law enforcement, and transnational crime. Similarities and differences in the concepts of security and defense can be seen from the regulations, the concepts used, the institutions and the constitution. This article shows that national resilience is influenced by national defense and security. The safe condition of a country is inseparable from the security and defense factors alone but is synergized with each other factors such as economic, political, legal, social, cultural, ideological, geographic, demographic and natural resources. Keywords: defense, national security, national resilience, security